Pengaruh Price, Place, Dan Direct Marketing Terhadap Purchase Decision Produk Serabut Kelapa Pada Rahma Craft Kabupaten Kediri - Adissya Nur Rahma; Moch. Saleh Udin; Taufik Akbar (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This research aims to explain and prove the hypothesis regarding whether there is an influence of price, place, and direct marketing on purchase decisions for coconut fiber products at Rahma Craft, Gurah District, Kediri Regency. This research uses descriptive research with quantitative methods with a sampling technique, namely non-probability sampling with an accidental sampling method with a population of 110 Rahma Craft consumers and a sample of 86 consumers. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, t test (partial), F test (simultaneous), and determinant coefficient (R2) which were processed using the SPSS version 26 program. The results of this research were obtained The conclusion is that price has a partial positive and significant effect on purchase decisions, with a significant t value of 0.001 < 0.05. Place has a positive and significant effect on purchase decisions, with a significant t value of 0.005 < 0.05. Direct marketing has a positive and significant effect on purchase decisions, with a significant t value of 0.001 < 0.05. Price, place, and direct marketing simultaneously have a positive and significant effect on purchase decisions for coconut fiber products at Rahma Craft, Gurah District, Kediri Regency, looking at the significant F value of 0.000 < 0.05.